The Interaction Between Suppliers and Fraudulent Customer Firms: Evidence from Trade Credit Financing of Chinese Listed Firms - Wu, Sirui; Gong, Guangming; Huang, Xin; Tian, Haowen (Journal of business ethics, 2022)
This study investigates the interaction between suppliers and fraudulent customer firms from the perspective of reputation damage and reputation recovery. Specifically, reputation damage from the regulatory penalty for corporate fraud induces the trust crisis and suppliers respond to fraudulent firms by reducing the trade credit supply. To repair a damaged reputation and rebuild the trust, fraudulent firms raise the ratio of prepayment to purchase volume when purchasing from small suppliers and increase the proportion of purchase from large suppliers in the next year. Channel analysis shows that the declining trust is one of potential mechanisms to reduce the trade credit. Furthermore, the negative effect is more pronounced for fraudulent firms with non-related party suppliers, higher supplier concentration, less analyst coverage, and for fraudulent firms located in regions with less-developed financial environment. Additionally, supplier sanctions have a spillover effect on non-fraudulent customer firms in the same industry. The conclusions are robust to a series of checks, including PSM–DiD, firm and year fixed effect, the alternative measure for trade credit financing, the industry-year fixed effect and the consideration of the monetary policy and financial crisis.